WASTE MANAGEMENT EFFORTS WITH 3R (REUSE, REDUCE, AND RECYCLE) AT STIKES KARSA HUSADA GARUT - Andhika Lungguh Perceka, Andhika Lungguh Perceka; N. Ai Erlinawati, N. Ai Erlinawati; Herlin Rusyani, Herlin Rusyani; Taufik Huda, Taufik Huda; Aceng Ali Awaludin, Aceng Ali Awaludin (Jurnal Medika Cendikia, 2025)
The issue of waste remains a serious environmental problem at the global, national, and local levels. Population growth, changes in consumption patterns, and increasingly practical lifestyles have led to a steady increase in the volume of waste over time. The objectives of this study are: To identify and analyze waste management efforts through the application of the 3R concept (Reduce, Reuse, and Recycle) at STIKes Karsa Husada Garut as a form of support for creating a clean, healthy, and environmentally conscious campus environment. This study was conducted using qualitative research methods by observing and collecting information about the research object. The study was conducted by observing and analyzing the behavior of people in the environment of STIKes Karsa Husada Garut. The study analyzed the effectiveness and suitability of waste separation. Based on our observations, we can conclude that waste management through the process of separating organic and inorganic waste is very important to address environmental, health, and economic issues related to waste. Although waste management efforts are carried out at STIKes KHG, observations show that its implementation is still poor. The STIKES KHG community must be educated about disposing of waste according to its type. Waste management is beneficial for reducing the impact of environmental pollution and supporting the waste management system. Our discussion also shows the importance of applying the 3R (Reduce, Reuse, Recycle) concept in everyday life to reduce the amount of waste produced. The process of recycling waste into various products has economic and environmental benefits. The importance of waste management is also reflected in the objectives of waste management in mathematics and natural sciences. However, the report shows that students' understanding and awareness of waste sorting needs to be improved to achieve good waste management. In addition, we also show the benefits of waste management in reducing the use of natural resources and preserving the environment.